Influence of Match Status on serve execution and technical-tactical behaviors in men`s performance volleyball - Maneiro, R.; Davila, A.; Casal, C. A.; Iván-Baragaño, I. (Frontiers in Psychology, 2026)
Introduction: The serve is one of the most important technical-tactical behaviors in men`s performance volleyball and, at the same time, one of the least studied. Therefore, the aim of this study was threefold: first, to analyze the usual practices of these actions; second, to examine the relationship between the variables considered using Match Status as the reference criterion; and finally, to determine, at a multivariate level, the influence of the predictor variables on Match Status.